The Clostridium difficile Cell Wall Protein CwpV Confers Phase-Variable Phage Resistance - Fairweather,NF; Sekulovic1,O; Bedoya,MO; Fivian-Hughes,A; Fortier,L-C (Molecular Microbiology, 2015)
Bacteriophages are present in virtually all ecosystems, and bacteria have developed multiple antiphage strategies to counter their attacks. Clostridium difficile is an important pathogen causing severe intestinal infections in humans and animals. Here we show that the conserved cell-surface protein CwpV provides antiphage protection in C. difficile. This protein, for which the expression is phase-variable, is classified into five types, each differing in their repeat-containing C-terminal domain. When expressed constitutively from a plasmid or the chromosome of locked ‘ON’ cells of C. difficileR20291, CwpV conferred antiphage protection. Differences in the level of phage protection were observed depending on the phage morphological group, siphophages being the most sensitive with efficiency of plaquing (EOP) values of < 5 × 10−7 for phages CD38-2, CD111 and CD146. Protection against the myophages MMP01 and CD52 was weaker, with EOP values between 9.0 × 10−3 and 1.1 × 10−1. The C-terminal domain of CwpV carries the antiphage activity and its deletion, or part of it, significantly reduced the antiphage protection. CwpV does not affect phage adsorption, but phage DNA replication is prevented, suggesting a mechanism reminiscent of superinfection exclusion systems normally encoded on prophages. CwpV thus represents a novel ubiquitous host-encoded and phase-variable antiphage system in C. difficile.